Determining senior secondary school teachers’ job performance in mathematics: Affective factors as a panacea - Badru, Ademola Kehinde (Universitas Negeri Yogyakarta, 2025)
Teachers’ factors is one of the factors that influencing students’ learning outcomes in mathematics at secondary school level observed. However, there is therefore needs for more research attention to be drawn to teachers’ job performance using some affective factors among the factors. Hence, this study therefore to investigate the mathematics teacher’s affective factors as a panacea for determining senior secondary school teachers’ job performance in mathematics in Ogun state. A descriptive survey research design and 203 public Senior Secondary Schools in Ogun East Senatorial Zone (Ijebu and Remo Block) of Ogun state, Nigeria was adopted. A total of 571 public teachers teaching mathematics in SSS were selected which contained male teachers were 306 (53.42%) and female teachers were 266 (46.58%); the qualified teachers were 424 (74.26%) and less qualified teachers were 147 (25.74%) and the experienced teachers were 426 (74.61%) and less experienced teachers were 145 (25.39%). Four instruments were employed to collect data for this study. Linear Multiple Regression Analysis was adopted to test for four statement of hypotheses formulated at 0.05 level of significance. The result revealed that the contribution of teachers’ stress management on senior secondary school mathematics teachers' job performance is little and significant (R2 = 0.023; F = 13.572; P < 0.05); Teacher’s stress management, Social abilities and teacher’s Motivation when combined together has little contribution on mathematics teachers’ job performance and significant (R2 = 0.039; F = 7.602; P < 0.05). It is therefore concluded that there is a statistically significant contribution of teachers’ stress management on senior secondary school mathematics teachers' job performance. One of the recommendations made is that Stakeholders should organize seminars and workshops and mandate mathematics teachers to attend at regular interval, to keep them abreast of modern trends in stress management healthy lifestyles and optimal performance.